Valuation of Non-Timber Forest Products Collected by Forest Dwellers of Surat Forest Circle of Gujarat State, India - Yadav, Rajkumar; Rajpurohit, Sweta; Kamboj, R. D. (Indian Forester, 2019)
In this study, an attempt has been made to estimate monetary value realized by local communities from non-timber forest products (NTFPs) collection from the protected forest of Surat Forest Circle (SFC) of Gujarat state. The study is based on survey of 10% households in the identified 10% forest villages as per stratified random sampling. The selection of forest village was done in the four different forest division of SFC. During the study a total of 26 (25 plant products and 1 insect product) types of NTFPs have been found in the SFC. The findings show that about ₹307.4 million/annum monetary value is realised from these 26 types of NTFPs. The maximum economic value was realised in the VFD (41.9%) followed by SFD (29.7%), NFD (25%) and BFD (3.5%). Furthermore, the NTFPs value has been calculated on the per hectare basis and is estimated to be Rs. 2086.0/annum, ₹1417.2/annum, ₹1359.5/annum and ₹452.5/annum for SFD, NFD, VFD and BFD, respectively. The analysis also showed that per capita and per household's monetary value varied in the all forest divisions. The study revealed that the NTFPs benefits contributes remarkably for the forest dwellers of different forest divisions in SFC.